Kampus Newsworthy dalam Perspektif Jurnalis di Surabaya - Lukman Hakim; Amabel Yuniar; Buga Rahmawati (Program Studi Ilmu Komunikasi Fakultas Dakwah dan Komunikasi, UIN Sunan Ampel Surabaya, 2022)
This paper aims to describe the symbolic reality of higher education based on journalists' viewpoints. This study focuses on uncovering the framing of news stories conducted by Jawapos.com, Detik.com, and Suarasurabaya.net pertaining to the educational issues of five public universities in Surabaya. Using quantitative content analysis and a thematic qualitative approach, the findings illustrate that Airlangga Univerity (Unair) is the university with the highest media visibility with 27 news articles published by those three news media, followed by Institut Teknologi Sepupuh November (ITS) and Universitas Negeri Surabaya (Unesa) with 12 news stories respectively. Meanwhile, Universitas Pembangunan Nasional Veteran Jatim (UPNVJ) and State Islamic University of Sunan Ampel (UINSA) are in both fourth and fifth rank, with each respective news article is 5 and 2. Further, in framing news, those three news media tend to frame campus reputations on aspects of leadership, academic performance, emotional appeal, social responsibility, innovation, and campus attitudes toward consumers.